Estimasi Jumlah Mismanaged Plactic Waste (MPW) Berdasarkan Kenaikan Populasi: Studi Kasus 30 Negara Tahun 2019-2022: Studi Kasus 30 Negara Tahun 2019-2022 - Muliawati, Triyana; Supmawati, Meysi; Rahmawati, Eli; Aula, Naila Tsamrotul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Abstract: Humans have produced more than 8 billion tons of plastic, more than half of which is directly dumped into landfills and only about 9% is recycled. This makes the author interested in looking at the relationship between population and the amount of waste generated in the hope of helping the government in reducing the amount of waste generated. This study aims to estimate the amount of Mismanaged Plastic Waste (MPW) based on population increase, focusing on 30 countries from 2019 to 2022. The Rank Spearman correlation test method was used to evaluate the relationship between population size and the amount of MPW, showing a strong relationship with a correlation coefficient of 0.60712. Furthermore, an analysis using the Cox-Stuart test was conducted to determine the trend in population size from 2003 to 2022, which showed that there was no clear trend in the population data or an upward trend in the time span. Based on these findings, a predictive estimate of the number of MPW for the period 2019-2020 was conducted, providing additional insight into the impact of population growth on the amount of unmanaged plastic waste in these countries.